Comb-shaped sulfonated poly(aryl ether sulfone) proton exchange membrane for fuel cell applications. (29th April 2022) - Liu, Lili; Lu, Yao; Ning, Cong; Li, Na; Chen, Shouwen; Hu, Zhaoxia
Abstract: Structure design is the primary strategy to acquire suitable ionomers for preparing proton exchange membranes (PEMs) with excellent performance. A series of comb-shaped sulfonated fluorinated poly(aryl ether sulfone) (SPFAES) membranes are prepared from sulfonated fluorinated poly(aryl ether sulfone) polymer (SPFAE) and sulfonated poly(aryl ether sulfone) oligomer (SPAES-Oligomer). Chemical structures of the comb-shaped membranes are verified by 1 H nuclear magnetic resonance (NMR) and Fourier transform infrared (FT-IR) spectra. The comb-shaped SPFAES membranes display more continuous hydrophilic domains for ion transfer, because the abundant cations and flexible side-chains structure possess higher mobility and hydrophilicity, which show significantly improved proton conductivity, physicochemical stability, mechanical property compared to the linear SPFAE membranes. In a H2 /O2 single-cell test, the SPFAES-1.77 membrane achieves a higher power density of 699.3 mW/cm 2 in comparison with Nafion® 112 (618.0 mW/cm 2 ) at 80 °C and 100% relative humidity. This work offers a promising example for the synthesis of highly branched polymers with flexible comb-shaped side chains for high-performance PEMs. Graphical abstract: Image 1 Highlights: Long comb-shaped sulfonate side-chains were incorporated by a facile synthetic rout. Enhanced water uptake and proton conductivity for comb-shaped PEMs. Good antioxidative stability was obtained due to the existence of C–F bonds. Highly branched ionomers for comb-shaped PEMs are beneficial to build continuous H + -channels. SPFAES-1.77 exhibited higher cell performance than Nafion® 112 at 80 °C.